Macrophages: Subtypes, Distribution, Polarization, Immunomodulatory Functions, and Therapeutics - Mengyuan Peng; Niannian Li; Hongbo Wang; Yaxu Li; Hui Liu; Yanhua Luo; Bao Lang; Weihang Zhang; Shilong Li; Liujun Tian; Bin Liu (MedComm)
ABSTRACT Macrophages are heterogeneous immune cells with diverse subtypes and tissue‐specific distributions, displaying dynamic polarization states that critically govern their immunomodulatory functions and responses to environmental cues. As key regulators of innate and adaptive immunity, they originate from either embryonic progenitors or bone marrow‐derived monocytes and exhibit remarkable plasticity in response to microenvironmental cues. Tissue‐resident macrophages (e.g., Langerhans cells, Kupffer cells, microglia) display unique organ‐specific functions, while inflammatory stimuli drive their polarization into proinflammatory (M1) or anti‐inflammatory (M2) phenotypes along a functional continuum. This review systematically examines macrophage subtypes, their anatomical distribution, and the signaling pathways (e.g., NF‐κB, STATs, PPARγ) underlying polarization shifts in acute and chronic inflammation. We highlight how polarization imbalances contribute to pathologies including neuroinflammation, liver fibrosis, and impaired tissue repair, particularly in aging contexts. Furthermore, we discuss emerging therapeutic strategies targeting macrophage plasticity, such as cytokine modulation, metabolic reprogramming, and subtype‐specific interventions. By integrating recent advances in macrophage biology, this work provides a comprehensive framework for understanding their dual roles in immune regulation and tissue homeostasis, offering insights for treating inflammatory and age‐related diseases through macrophage‐centered immunomodulation.